Análisis financiero y la auditoría como gestión en una empresa comercial Comercio Iquitos E.I.R.L. - 2019 - Oroche Inga, Jonathan (2022)
A know, that a high attention in the fulfillment of the amortization payments of the received financings, give to the company a stability and financial confidence in front of third parties, for that reason the investigation of Financial analysis and the audit of management in a commercial company, trade Iquitos EIRL-2019, being this investigation of qualitative- descriptive type, whose population of study was of 30, between entrepreneurs and accountants of the same commercial turn, belonging to this economic activity according to ISIC, as a conclusion we have a favorable opinion regarding the compliance policy in the payment to third parties and banking entities, this is reflected that ñthe company that is a good payer in the financial system has a good image in the infocor system at national level and is apt to obtain credit at any time. It is adequate in terms of indebtedness capacity, better if the respondents know that these ratios of their financial statement analysis have been obtained through a management audit, hence the importance that every commercial company should have an audit office, one to protect its assets and two to give validity to the financial statement analysis that apply in each said states.